The Gift Collecting Entanglements & Embodied Histories - Yap, June (Singapore Art Museum, 2021)
The Gift is part of a broader project titled Collecting Entanglements and Embodied Histories that is developed as a dialogue between collections of four museums. The conversation extend into four related exhibitions that include artwork exchanges. This exploration of collections also uncovers histories of collecting-of gifts received, rare discoveries unearthed, and acknowledgements of significance. As with the gift, the value of those accumulated objects confer upon the collection stature and prestige, but also impose a duty of care and responsibility for these riches.